Our own, non-invasive method of measuring the cardiac output (CO) and stroke volume (SV) in children aged 7–9 during physical exercise - Szubert, Józef; Szubert, Sławomir; Wieczorek, Wojciech; Szymańska-Paszczuk, Alicja; Ziółkowski, Włodzimierz; Szubert, Marietta (Biospołeczne uwarunkowania uczestnictwa w kulturze fizycznej i zdrowotnej osób w różnym wieku, 2017)
Introduction: Cardiac output (CO) determines the cardiovascular system’s function and undergoes fluctuations in various physiological and pathological states. All of the currently available CO monitoring methods have their limitations, which is the reason we keep looking for new, possibly simple, cost-effective and safe, but still reliable methods.Materials and methods: Based on both our own and global empiric data and laws of thermodynamics and fluid dynamics, we developed a new, non-invasive and safe method of measuring cardiac output and the stroke volume (SV). The aforementioned method allows us to measure both CO and SV in children undergoing various relative workload exercise.Results: CO and SV values obtained by the author’s method do not differ significantly from the values obtained by other researchers using different methods.Conclusions: The developed method is non-invasive, simple, cost-effective, reliable and poses no risk for the examined person’s life or health. It can be a viable alternative to the currently used methods.